2020
DOI: 10.2196/17699
|View full text |Cite
|
Sign up to set email alerts
|

Using Smart Bracelets to Assess Heart Rate Among Students During Physical Education Lessons: Feasibility, Reliability, and Validity Study

Abstract: Background An increasing number of wrist-worn wearables are being examined in the context of health care. However, studies of their use during physical education (PE) lessons remain scarce. Objective We aim to examine the reliability and validity of the Fizzo Smart Bracelet (Fizzo) in measuring heart rate (HR) in the laboratory and during PE lessons. Methods In Study 1, 11 healthy subjects (median age 22.0 y… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
0
13
0
1
Order By: Relevance
“…According to a number of studies, AI sports equipment with exercise programs may increase positivity [ 8 , 9 ]. Among them, smart sports bracelets are a commonly used intelligent wearable device in sports today [ 10 , 11 ]. By collecting data and browsing health records, sports smart bracelets can monitor physiological data during exercise [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to a number of studies, AI sports equipment with exercise programs may increase positivity [ 8 , 9 ]. Among them, smart sports bracelets are a commonly used intelligent wearable device in sports today [ 10 , 11 ]. By collecting data and browsing health records, sports smart bracelets can monitor physiological data during exercise [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different CHITs apps were offered through the Apple Store and Google Playstore for various health concerns [23]. Recently CHITs apps and accessories such as smart bands and wristwatches became available and favoured among health-conscious consumers [24,25]. The available CHITs apps and accessories perform health monitoring, physiological activity tracking, notification, heart rate recording, and sleep and mental health monitoring [3,4,5,15,17,24,26,27,29,30].…”
Section: Consumer-oriented Health Information Technologies (Chit)mentioning
confidence: 99%
“…Recently CHITs apps and accessories such as smart bands and wristwatches became available and favoured among health-conscious consumers [24,25]. The available CHITs apps and accessories perform health monitoring, physiological activity tracking, notification, heart rate recording, and sleep and mental health monitoring [3,4,5,15,17,24,26,27,29,30]. A complete and detailed report can be quickly produced to help users monitor their health conditions [29].…”
Section: Consumer-oriented Health Information Technologies (Chit)mentioning
confidence: 99%
“…Electrocardiography (ECG) and Polar HR monitors are generally used for HR monitoring [4][5][6]. However, ECG is more suitable for laboratory and hospital settings than for individual use, and wearing a Polar HR chest strap involves a very complex process.…”
Section: Introductionmentioning
confidence: 99%
“…As wearable devices become more common, it is critical that they produce reliable and valid data. In terms of HR measurement, many peer-reviewed studies have been conducted to evaluate the reliability and validity of wearable devices produced by different brands, such as Fizzo, Fitbit, Apple Watch, and Garmin [6,[12][13][14][15][16][17]. Some studies have shown that these devices more accurately measure HR at lower treadmill speeds [18][19][20]; however, others have shown that they are more accurate at higher treadmill speeds [21].…”
Section: Introductionmentioning
confidence: 99%